1991
DOI: 10.1063/1.460308
|View full text |Cite
|
Sign up to set email alerts
|

Tunable far-infrared laser spectroscopy of deuterated isotopomers of Ar–H2O

Abstract: Several far-infrared vibration-rotation-tunneling transitions have been measured in deuterated isotopomers of Ar–H2O for the first time. These experimental results will enable the generation of improved intermolecular potential energy surfaces for the Ar–H2O system when combined with existing microwave, far-infrared, and infrared data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 14 publications
1
21
0
2
Order By: Relevance
“…The water-methanol dimer is the latest, and one of the most chemically complex, in a series of water-containing, hydrogen-bonded dimers studied in our laboratories by microwave and far-infrared spectroscopy, for the purpose of fitting the observed spectra to intermolecular potential energy surfaces ͑IPSs͒. [1][2][3][4][5][6][7][8][9][10][11] The complex formed between methanol and water is particularly interesting because both hydrophobic and hydrophilic forces contribute strongly to the IPS of this relatively small dimer, creating a high degree of anisotropy. In addition, the watermethanol dimer will provide a test of the adaptability of the IPSs of simpler dimers to larger, multi-functional interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The water-methanol dimer is the latest, and one of the most chemically complex, in a series of water-containing, hydrogen-bonded dimers studied in our laboratories by microwave and far-infrared spectroscopy, for the purpose of fitting the observed spectra to intermolecular potential energy surfaces ͑IPSs͒. [1][2][3][4][5][6][7][8][9][10][11] The complex formed between methanol and water is particularly interesting because both hydrophobic and hydrophilic forces contribute strongly to the IPS of this relatively small dimer, creating a high degree of anisotropy. In addition, the watermethanol dimer will provide a test of the adaptability of the IPSs of simpler dimers to larger, multi-functional interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The shift in the Ar-HOD vibrational origin from the HOD monomer origin is assumed to have the same value as the corresponding shift in the Ar-H 2 O system, i.e., 3.12 cm Ϫ1 . 12 Blake and co-workers 25 have measured the energy of the ⌸(1 01 ) state with respect to the lowest ⌺(0 00 ) in ArϪHOD in the far IR to be 19.90 cm Ϫ1 . The corresponding energy splitting between the ⌺(1 01 ) and ⌸(1 01 ) states, however, has not been measured experimentally but has been calculated using the Ar-H 2 O potential energy surface 13 to be 10.89 cm Ϫ1 .…”
Section: A Overtone Spectroscopy Of the Ar-hod Complexmentioning
confidence: 98%
“…The corresponding energy splitting between the ⌺(1 01 ) and ⌸(1 01 ) states, however, has not been measured experimentally but has been calculated using the Ar-H 2 O potential energy surface 13 to be 10.89 cm Ϫ1 . 25 In predicting the position of the Ar-HOD band it was assumed that the rotational spacings are the same for v OH ϭ0 and v OH ϭ3 vibrational states of Ar-HOD.…”
Section: A Overtone Spectroscopy Of the Ar-hod Complexmentioning
confidence: 99%
“…The inversion-tunneling of NH3 was originally included by a simple two-state model, but presently we have extended our formalism and computer codes with a basis for the NH3 umbrella coordinate, so that we can include explicitly the U2 vibration and the inversion-tunneling of the NH3 monomer in the Ar-NH3 complex. The results are extensively described in recent papers by Van Bladel et al [86,87] and compared in detail with experimental d ata [78][79][80][81][82][83][84][85], Since the topic of Van der Waals molecules will be covered in this workshop by Hutson and by Brechignac, I have limited myself here to a summary of the main conclusions. It has been found that, indeed, the spectra of these Van der W aals complexes are extremely sensitive to the shape of the potential surface in the entire attractive region.…”
Section: Experim Ent Spherical Expansionmentioning
confidence: 99%
“…(1 1 ), we have applied them to the calculation of the microwave and farinfrared spectra of Ar-NH3 [67,[78][79][80][81][82], Ar-H^O [83,84] and A r-D 20 [82,85]. For the latter system we had first to transform the Ar-TI20 potential to a different center of mass.…”
Section: Spectra Op Van Der Waals Moleculesmentioning
confidence: 99%